Mapping the Scientific Structure of Medical and Laboratory Equipment Patents in USPTO database between 1984 and 2014 - Maryam Emami; Nosrat Riahinia; Faramarz Soheili (Tehran University of Medical Sciences, 2019)
Background and Aim: The purpose of this study was to analyze the co-occurrence of the terms of medical and laboratory equipment patents in the United States Patent and Trademark Office between 1984 and 2014. Materials and Methods: This research was an applied study using scientometrics and co-word analyses. The statistical population of the present study included all patents of medical and laboratory equipment registered in the United States Patent and Trademark Office database between 1984 and 2014. As a result, a total of 13424 patents were retrieved. Results: The results revealed that in terms of frequency, the keyword "Menstrual Fluid" and in terms of co-occurrence, two keywords (Menstrual Fluid and Magnetic Resonance Image Apparatus) were the most frequent ones in medical and laboratory equipment studies. The results of hierarchical clustering with "Wardchr('39')s method" led to the formation of eight clusters in this area including the following: General Equipment, Rehabilitation Equipment, Dental Equipment, Therapeutic Equipment, Emergency Equipment, Laboratory Equipment, Diagnostic Equipment, and Medical Consumables. Conclusion: The analysis of the co-occurrence of words revealed the scientific structure of medical and laboratory equipment well. Accordingly, the scientific issues were extracted and the relationship between them was discovered. The maps of co-word analysis showed several changes, sustainability of concepts, and terms related to this field of science.